Dynamic electrowetting and dewetting of ionic liquids at a hydrophobic solid-liquid interface - Li, H.; Paneru, M.; Sedev, Rossen; Ralston, J. (American Chemical Society, 2013)
The dynamic electrowetting and dewetting of ionic liquids are investigated with high-speed video microscopy. Five imidazolium-based ionic liquids ([BMIM]BF4, [BMIM]PF6, [BMIM]NTf2, [HMIM]NTf2, and [OMIM]BF4) are used as probe liquids. Droplets of ionic liquids are first spread on an insulated electrode by applying an external voltage (electrowetting) and then allowed to retract (dewetting) when the voltage is switched off. The base area of the droplet varies exponentially during both the electrowetting and retraction processes. The characteristic time increases with the viscosity of the ionic liquid. The electrowetting and retraction kinetics (dynamic contact angle vs contact line speed) can be described by the hydrodynamic or the molecular-kinetic model. Energy dissipation occurs by viscous and molecular routes with a larger proportion of energy dissipated at the three-phase contact line when the liquid meniscus retracts from the solid surface. The outcomes from this research have implications for the design and control of electro-optical imaging systems, microfluidics, and fuel cells.